Sejarah dan Perkembangan Institut Agama Kristen Negeri (IAKN) Tarutung Kampus Agama Kristen di Silangkitang - Sinaga, Arawna Olivia Marito; Siringo-ringo, Angelina; Sigalingging , Herlina P.; Tanjung, Yushar; Hidayat, Hidayat; Sidiq , Ricu (Innovative: Journal Of Social Science Research, 2024)
Tarutung State Christian Institute (IAKN) is one of the State Christian Universities on the island of Sumatra, namely North Sumatra Province. The Tarutung State Institute of Christian Religion (IAKN) Campus is Christian, which means that the Christian Religious Campus has students who study Christian Religious education and knowledge at the Tarutung State Christian Religious Institute (IAKN) Campus not only from one belief in the church, but from various respective beliefs. -each in one place, namely the Church. Tarutung State Christian Institute (IAKN) is capable of producing and creating Alumni Graduates by integrating the abilities of each alumni with their respective fields and expertise. The Tarutung State Christian Religion Institute (IAKN) has a very large collaborative relationship which has an impact on cooperation agreements between the Church, Government and Private Agencies, and also social workers. The Tarutung State Christian Religion Institute created a curriculum that is used to support lecture material and is able to produce alumni graduates who can work in institutions based on the interests and talents of each student.